Problematic issues of enterprises profit management in Ukrainian scientific sources:the state of coverage - Kotliar, Daryna; Turlakova, Natalia (My University, 2023)
The theses is devoted to the literature review of the current problems of enterprises profit management in UA scientific sources over last 8 years. The study recognized, analyzed, and synthesized prior work by researchers.
Keywords: profit; profit management; strategic management; economic conditions; theoretical methods